(untitled) (Plant Tissue Culture and Biotechnology, 2009)
Efforts have been made to establish a protocol for direct multiple shoot regeneration from both in vitro grown seedlings and mature plants of Citrus macroptera. Both nodal and shoot tip explants taken from in vitro grown seedlings were cultured in MS supplemented with different concentrations of BAP and Kn either singly or in combinations. Both these explants are capable to regenerate and produce in vitro multiple shoots. Maximum number of shoots were obtained from nodal explants in MS supplemented with 1.0 mg/l BAP. BAP alone was found superior to Kn. On the other hand, only nodal explants from mature plants were used and 1.0 mg/1 BAP was also found best suitable for shoot induction and multiplication. Ex vitro rooting in pot soil (mixed with biogas slurry derived from cow-dung) was most successful compared to in vitro rooting in half strength of MS supplemented with different concentrations of NAA and IBA. Key words: In vitro, Shoot regeneration, Citrus macroptera D.O.I. 10.3329/ptcb.v18i1.3246 Plant Tissue Cult. & Biotech. 18(1): 17-24, 2008 (June)